Pelaksanaan Pembelajaran Pendidikan Agama Islam dalam Pembinaan Karakter Mandiri Anak Autis di SLB Negeri 1 Panti - Ali Imran (Kampus Akademik Publiser, 2025)
This research aims to find out how the process of implementing Islamic Religious Education Learning in developing the independent character of autistic children and to find out the factors that cause the slow independence of autistic children. This research is a qualitative descriptive research, the informants in this research are the Islamic Education Teacher at SLB Negeri 1 Panti, two guardians class, head of curriculum and principal of SLB Negeri 1 Panti. Data was collected by observing, interviewing and documenting. The results of the research show that: he preparation of an Islamic religious education learning program in developing the independent character of autistic children is carried out by preparing appropriate materials, appropriate methods, and evaluating learning. Implementation of Islamic religious education learning in developing the independent character of autistic children is carried out by instilling moral values ​​using demonstration methods and direct question and answer. The learning process is carried out based on: subject matter, methods, objectives and learning evaluation. The factors that cause the slow independence of autistic children are caused by several things, such as the habit of autistic children asking for help from others, the influence of friends, teachers who do not understand the character of autistic children and the lack of direction from parents in developing the independent character of autistic children.